Profiling Students’ Creative Thinking Skills On The Digestive System Topic: A Study Using Torrance’s Framework - Tifanny Safitri; Surti Kurniasih; Indarini Dwi Pursitasari (Universitas Sultan Ageng Tirtayasa, 2026)
Creative thinking is an essential 21st-century skill that enables students to approach complex problems with originality, flexibility, and depth. However, its development in Indonesian science classrooms remains limited. This study analyzed junior high school students' creative thinking profiles on the digestive system using Torrance's framework, which includes fluency, flexibility, originality, and elaboration. A total of 108 eighth-grade students in Bogor participated in the study. Data were collected through essay tests and semi-structured teacher interviews and analyzed using descriptive statistics and thematic analysis. Results revealed a low level of creative thinking, with an average score of 36.75%. Originality scored the highest (43.58%), while flexibility was the lowest (30.66%). Students showed difficulties generating multiple ideas, viewing problems from different perspectives, and developing ideas in detail. Teacher interviews confirmed that creative thinking was not explicitly taught, and procedural tasks mostly dominated learning activities. This study offers insight into how biology learning environments can reveal the strengths and gaps in students’ creative thinking. The findings are expected to inform future learning designs that aim to foster creativity and critical thinking in science education and may serve as a basis for integrating STEM-oriented approaches more effectively.